Enhanced Flexible Mold Lifetime for Roll‐to‐Roll Scaled‐Up Manufacturing of Adhesive Complex Microstructures. Issue 2 (20th November 2022) - Kim, Jae‐Kang; Krishna‐Subbaiah, Nagaraj; Wu, Yingdan; Ko, Jongkuk; Shiva, Anitha; Sitti, Metin
Abstract: Various functional complex 3D patterned surfaces with micro‐ or nanostructures have been developed and their superior performances over non‐patterned smooth surfaces proven. However, it is challenging to mass‐produce such complex micro‐/nanopatterned surfaces, which limits their commercialization drastically. Although roll‐to‐roll (R2R) manufacturing using flexible molds has been implemented for mass‐production of such functional surfaces, the poor mold repeatability issue has not been resolved yet. Here, a strategy to significantly improve the repeatability of the micropatterned flexible silicone molds over 1000 cycles against highly adhesive polyurethane acrylates (PUAs) in UV light curing based R2R systems by using a two‐step curing process is reported. The mold repeatability is drastically increased from 10s of cycles to over 1000 cycles through the proposed strategy in spite of the complicated 3D undercut geometry and high tackiness of the microstructure. This two‐step process would enable scaled‐up production of micro‐/nanostructured adhesives, such as gecko‐inspired microfiber adhesives as demonstrated in this study, as well as various other functional micro‐/nanostructured surfaces by enhancing the flexible mold lifetime. Abstract : A two‐step curing technique, including an incomplete curing process and a post‐curing process, is presented as a strategy to enhance the flexible mold lifetime in UV‐curing‐based roll‐to‐roll manufacturing systems. By utilizing the technique, silicone molds patterned with complex adhesive microstructures are replicated over 1000 cycles by highly adhesive polyurethane acrylate materials.